Bilateral symmetric Merkel cell carcinomas of the dorsal hands: multiple primary tumors or early metastasis? - Seyffert, Jennifer; Herman, Alysa; Katz, Brian; Rivlin, Daniel (International Journal of Research in Dermatology, 2021)
Merkel cell carcinoma (MCC) is an aggressive and uncommon neuroendocrine tumor which clinically presents as a rapidly growing solitary nodule or plaque located in sun exposed areas on the head, neck, and extremities. Merkel cell carcinomas can be UV-induced or result from viral infection with the Merkel cell polyomavirus (MCV). We present a unique case of bilateral symmetric Merkel cell carcinomas located on the dorsal hands and briefly discuss options for genomic investigation to delineate if the tumors are multiple primary tumors or result of metastatic disease.